Pelatihan Dan Pembuatan Proposal Untuk Hibah Dan CSR Di Desa Cupak Jombang - Viviane Maharani; Glorya Oktavianti; Alifia Mutiara; Dewa Ayu Chittanirmala Mahadharma; Awalita Ariyani Sujarno; Muhammad Zidan Fadillah Yulkhaq; Maulidah Narastri; IGN.Andhika Mahendra (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
In the sense of the word, a proposal is a plan, or a formal proposal. The proposal is then discussed by the parties involved in the proposal. After discussion, the parties involved can determine whether the proposal is feasible or not. Matters such as methodology, research position, research roadmap, and the novelty of the research are the things that will be studied. Apart from being a consideration of whether the research being carried out is feasible or not, the proposal also serves as a direction for researchers who will conduct research. Grant proposals are the same as proposals in general, aimed at directing researchers to conduct research. However, grant proposals have a specific purpose, namely as a medium used by researchers to obtain grants. Therefore, Grant proposals must be detailed from the idea to the draft budget.